The Influence of Education and Training on Productive Skills, Nature of Work and Gender Inequality - Eugen GHIORGHIŢĂ (Annals of Spiru Haret University Economic Series, 2015)
The present paper is a synthesis of researching the evolution of gender discrimination during 2002-2013, i.e. the inclusion of women in the three levels of the national education system and the effects of education materialized in the degree of female population insertion on the labour market at national and European level.